Repair of acute respiratory distress syndrome by stromal cell administration (REALIST) trial: A phase 1 trial. (November 2021) - Gorman, Ellen; Shankar-Hari, Manu; Hopkins, Phil; Tunnicliffe, William S.; Perkins, Gavin D.; Silversides, Jonathan; McGuigan, Peter; Krasnodembskaya, Anna; Jackson, Colette; Boyle, Roisin; McFerran, Jamie; McDowell, Cliona; et al.
Abstract: Background: Mesenchymal stromal cells (MSCs) may be of benefit in acute respiratory distress syndrome (ARDS) due to immunomodulatory, reparative, and antimicrobial actions. ORBCEL-C is a population of CD362 enriched umbilical cord-derived MSCs. The REALIST phase 1 trial investigated the safety and feasibility of ORBCEL-C in patients with moderate to severe ARDS. Methods: REALIST phase 1 was an open label, dose escalation trial in which cohorts of mechanically ventilated patients with moderate to severe ARDS received increasing doses (100, 200 or 400 × 10 6 cells) of a single intravenous infusion of ORBCEL-C in a 3 + 3 design. The primary safety outcome was the incidence of serious adverse events. Dose limiting toxicity was defined as a serious adverse reaction within seven days. Trial registration clinicaltrials.gov NCT03042143. Findings: Nine patients were recruited between the 7th January 2019 and 14th January 2020. Study drug administration was well tolerated and no dose limiting toxicity was reported in any of the three cohorts. Eight adverse events were reported for four patients. Pyrexia within 24 h of study drug administration was reported in two patients as pre-specified adverse events. A further two adverse events (non-sustained ventricular tachycardia and deranged liver enzymes), were reported as adverse reactions. Four serious adverse events were reported (colonic perforation, gastric perforation, bradycardia and myocarditis) but none were deemed related to administration of ORBCEL-C. At day 28 no patients had died in cohort one (100 × 10 6 ), three patients had died in cohort two (200 × 10 6 ) and one patient had died in cohort three (400 × 10 6 ). Overall day 28 mortality was 44% ( n  = 4/9). Interpretation: A single intravenous infusion of ORBCEL-C was well tolerated in patients with moderate to severe ARDS. No dose limiting toxicity was reported up to 400 × 10 6 cells. Funding: The trial was funded by the Wellcome Trust Health Innovation Challenge Fund [Reference 106939/Z/15/Z].